Comparison Between Nr4a Transcription Factor Regulation and Function in Lymphoid and Tumor Treg Cells - Sekiya, Takashi (Frontiers in Immunology, 2022)
Although the "lymphoid" function of regulatory T (Treg) cells is crucial for organismal homeostasis, these cells are also known to suppress the antitumor immune response in the tumor microenvironments. Thus, a detailed understanding of Treg cell maintenance and function in both lymphoid organs and tumor environments may help to establish novel methods for the reactivating antitumor immunity, while retaining necessary immune tolerance towards self and non-hazardous antigens. Previous studies have hypothesized that Treg cells behave similarly in lymphoid organs and tumor environments; however, very few studies have specifically investigated Treg activity in these tumor environments. In addition, several recent studies identified a novel mechanism regulating Treg cell function in tumor environments. Our group has also previously described the critical roles of the Nr4a family of nuclear orphan receptors, comprising Nr4a1, Nr4a2, and Nr4a3, in the differentiation and maintenance of Treg cells in lymphoid organs. Subsequent evaluations have found that Nr4a factors help to maintain Treg cell function in tumor environments, thereby playing a suppressive role in T cell mediated antitumor immunity. Importantly, there were some obvious differences between the activities of these Nr4a factors under these conditions, including the specific function of the COX/PGE2 axis in tumor environments. This review was designed to investigate the role of Nr4a factors in the regulation of Treg cell activities both in the lymphoid organs and tumor environments, highlighting the commonalities and differences between these two different environments.